2021
DOI: 10.3390/land10121354
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Approach to Assess the Potential of Forest Areas for Therapy Services

Abstract: The study considers forest therapy as a tool for diversification of forest management. An up-to-date integrated approach for assessing and mapping potential of forest areas which could provide conditions for forest therapy services is developed and tested. It is based on combining data from the traditional forest inventory in Bulgaria and other open databases with methods for integrated assessment and mapping of ecosystem services: 7 criteria groups and 22 indicators are proposed, rated on a 5-point scale. Ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 46 publications
0
10
0
1
Order By: Relevance
“…Psychological benefits in environments with natural factors are widely reported from lowland greenspaces to highlands (131)(132)(133)(134)(135), and several studies have suggested a altitudinal effect on mood, emotion, cognitive function and behavior (136)(137)(138)(139)(140). Spending time at high altitudes reportedly has physiological benefits (141)(142)(143)(144)(145)(146)(147)(148)(149)(150) and previous studies adopted outdoor settings >1,500 m to observe apparent changes in pulmonary, cardiac, circulatory, metabolic, and inflammatory outcomes (141,145,151,152). There are multiple potential mechanisms linking altitude with psychophysiological responses, and the observed difference is possibly consequence of the varied altituderelated mechanisms involved in psychological and physiological restoration.…”
Section: Discussionmentioning
confidence: 99%
“…Psychological benefits in environments with natural factors are widely reported from lowland greenspaces to highlands (131)(132)(133)(134)(135), and several studies have suggested a altitudinal effect on mood, emotion, cognitive function and behavior (136)(137)(138)(139)(140). Spending time at high altitudes reportedly has physiological benefits (141)(142)(143)(144)(145)(146)(147)(148)(149)(150) and previous studies adopted outdoor settings >1,500 m to observe apparent changes in pulmonary, cardiac, circulatory, metabolic, and inflammatory outcomes (141,145,151,152). There are multiple potential mechanisms linking altitude with psychophysiological responses, and the observed difference is possibly consequence of the varied altituderelated mechanisms involved in psychological and physiological restoration.…”
Section: Discussionmentioning
confidence: 99%
“…However, at the regional and local scale, more detailed and reliable sources are needed. The Forest Inventory database at the level of subdivisions provides good quality data for forest ecosystems which are appropriate mapping units for this ecosystem type (Dodev et al, 2021).…”
Section: Identification and Mapping Of Ecosystem Typesmentioning
confidence: 99%
“…The studies focused on the assessment of RRCES are much more in Bulgaria (Nedkov et al 2014;Nedkov et al 2018;Ihtimanski et al 2020;Hristova and Stoycheva 2021;Hristova 2020;Dodev et al 2021;Grigorov et al 2021;Nedkov et al 2021a;Nedkov et al 2021b;Nedkov et al 2022;Silvestriev et al 2021;Zhiyanski et al 2021;Nikolova et al 2021b;Nikolova et al 2021c) than those on the accounting of these services, and very few of them are dealing with the protected areas (Assenov et al 2016b). However, in most of the published papers, the accounts referee the mountain ecosystems (Koulov et al 2017;Assenov et al 2017;Assenov et al 2016a;Ivanova et al 2016;Grigorov and Assenov 2015;Assenov et al 2016b).…”
Section: Introductionmentioning
confidence: 99%
“…Capacity of the mountain ecosystems in Bulgarian National Parks to generate flow of RRCES.The codes of the ecosystem services are given in table 2. (afterNikolova et al 2021)…”
mentioning
confidence: 99%